ISLAMISASI ILMU VERSUS INTEGRASI-INTERKONEKSI: TELAAH KEPUSTAKAAN TERHADAP PARADIGMA KEILMUAN ISLAM (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to comparatively analyze the paradigms of Islamization of knowledge and integration–interconnection in the development of contemporary Islamic scholarship. The research employs a qualitative method with a library research approach by analyzing classical and contemporary literature relevant to both paradigms. The findings indicate that the Islamization of knowledge and integration–interconnection differ fundamentally in their epistemological and methodological aspects; however, both originate from a shared concern regarding the value crisis in the development of modern science. The Islamization of knowledge emphasizes an epistemological reconstruction based on tawhid, positioning revelation as the primary source of knowledge, whereas the integration–interconnection paradigm focuses on dialogue and cross-disciplinary collaboration to construct a holistic and contextual understanding. This study finds that the two approaches are not dichotomous but rather complementary. A synthesis between the Islamization of knowledge and integration–interconnection has the potential to generate a paradigm of Islamic scholarship that is not only socially relevant and innovative but also ethically and spiritually meaningful. These findings are expected to provide a conceptual contribution to the development of Islamic education and knowledge that is responsive to global challenges.